New polyoxygenated fatty acid ester and other constituents from Dendrobium nobile Lindl. and their chemotaxonomic significance - Ting Chen; Dan Zhang; Xiujuan Fu; Siwei Chen; Hui Lei; Xiaoxu Bi (Biochemical Systematics and Ecology, 2026)

Machine learning prediction and analysis for LFL of C0-C2 combustible gases and blends under wide operating conditions - Mingkun Zhang; Wenchao Zhu; Dan Shen; Xiangyu Meng; Wuqiang Long; Mingshu Bi (Journal of Cleaner Production, 2026)

Platelet-based biomimetic nanoparticle-loaded hydrogels targeting tumor angiogenesis and cancer stem cells to prevent postoperative hepatocellular carcinoma recurrence - Zhe Li; Jinshuai Lan; Liyan Sun; Zhijun Bi; Wenlong Nie; Minquan Zhang; Dan Hu; Tong Zhang; Yue Ding (Chemical Engineering Journal, 2026)

Effect of explicit intermediate layer on the solution accuracy of the thermal stress for printed circuit heat exchangers with the homogenization method - Xiaoxu Zhang; Zirui Xu; Enhui Li; Yin Tan; Jiyuan Bi; Dan Zheng; Sheng Wang; Ting Ma (Annals of Nuclear Energy, 2026)

Genomic and genetic insights into the divergence between indica and japonica rice - Xiangxi Zhuansun; Wenlong Guo; Siqi Xia; Jun Shu; Kai Wang; Qiyu Zhang; Hao Wen; Lina Du; Siyu Wen; Ge Gao; Junran Wang; Dan Wang; et al. (Science Bulletin, 2026)

Seven previously undescribed seco-abietane and seco-isopimarane type diterpenoids from Biscogniauxia sp. and their biological activities - Meng Zhang; Yang Yan; Wen-Song Bi; Liu-Yang Ma; Dan Hu; Liang-Dong Guo; Zuo-Cheng Qiu; Guo-Dong Chen; Huan Zhao; Hao Gao (Phytochemistry, 2026)

Engineering boronation mixed-layer coating on polyanion cathode material with self-driven electronic reconstruction for long-life sodium-ion batteries - Hongwei Bi; Ruiyi Li; Xia Sun; Xiaoen Wang; Dan Luo; Zhongwei Chen (Chemical Engineering Journal, 2026)

Six previously undescribed bisabolane-type sesquiterpenes from marine derived fungus Aspergillus sp. WHUF04-170 and their antimicrobial activity - Wen-Juan Ding; Hong-Ming Huang; Yu-Ning Liu; Dan-Mei Tian; Ya-Qi Yuan; Ya-Xin Xue; Kui Hong; Hong-Kai Bi; Jin-Shan Tang (Phytochemistry, 2026)

Phytochemical constituents of the branches and leaves of Callicarpa pedunculata R. Br. and their taxonomic distribution - Chenyu Guo; Yimiao Chen; Limin Chen; Feifei Bi; Xinying Zhang; Ruiying Liu; Keying Xu; Antao Luo; Dan Yan; Guijuan Zheng (Biochemical Systematics and Ecology, 2026)

Dual-vortex shear layer dynamics and critical reynolds number threshold for stabilizing low-frequency oscillations in a low-emission conical vortex combustor - Dan Du; Jing-jie Ren; Qiang-qiang Hao; Jing-hao Zhang; Ming-shu Bi (Fuel, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Multivalent copper-carbon-catalyzed persulfate/O2 system: The relation between copper valence and the species of reactive oxygen - Zehui Fan; Zhisen Li; Dan Mo; Jingyang Zhang; Shuyi Yang; Yun Li; Changlong Bi; Chong Peng; Tao E (Journal of Environmental Chemical Engineering, 2025)

Specnuezhenide mitigates tunicamycin-induced liver injury in mice via ER stress modulation and metabolic reprogramming - Tianle Zhang; Dan Bi; Jiahui Li; Xin Jin; Huijuan Wu; Changyuan Yang; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Molecular Biology Reports, 2025)

Constitutive androstane receptor activation modulates YAP expression and activity through ubiquitination and sumoylation - Fengting Liang; Shuaishuai Zhang; Wenhong Zhou; Guofang Bi; Xiao Yang; Peng Wang; Shicheng Fan; Shuang Hu; Chenghua Wu; Xiaowen Jiang; Dan Li; Hui Ouyang; et al. (Toxicology Letters, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Numerical investigation on explosion limits of NH3/C2H5OH blends: Effects of NH3 cracking and initial components - Dan Shen; Menglan Miao; Xinyang Tian; Wenchao Zhu; Mingkun Zhang; Xiangyu Meng; Mingshu Bi (Process Safety and Environmental Protection, 2025)

Experimental and numerical study on flame instabilities of methanol blended with ammonia cracked gas under CO2 dilution at elevated ambient conditions - Xianrong Wu; Wenchao Zhu; Mingkun Zhang; Xuanrui Zhang; Dan Shen; Zechuan Cui; Xiangyu Meng; Mingshu Bi (Fuel, 2025)

Loperamide-induced constipation is associated with excessive accumulation of bile acids and cholesterol in the liver of mice; attenuation by hesperidin - Jiahui Li; Dan Bi; Ya Nie; Huijuan Wu; Yuting Lei; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Food and Chemical Toxicology, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Inhibitory effect and mechanism of lipopeptide Iturin A on food spoilage yeasts - Zhemin Li; Wencheng Jiao; Xiufang Bi; Xinyao Xie; Dan Shu; Di Luo; Jie Yang; Zhiying Yan; Hong Tan (Food Bioscience, 2025)

Production of fucose-rich exopolysaccharides by UV-mutated Enterobacter: Optimization, structural characterization and functional properties - Zhemin Li; Shuning Ren; Xiufang Bi; Dan Shu; Di Luo; Jie Yang; Xin Li (Food Bioscience, 2025)

IGF2BP3 suppresses ferroptosis in lung adenocarcinoma by m6A-dependent regulation of TFAP2A to transcriptionally activate SLC7A11/GPX4 - Pengpeng Li; Dan Chu; Guangcheng Ding; Dehua Qin; Yajing Bu; Bi Tian (Molecular and Cellular Biochemistry, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Experimental and numerical investigation of the combustion behavior in a conical vortex combustor - Dan Du; Jing-hao Zhang; Qiang-qiang Hao; Jing-jie Ren; Ming-shu Bi (Fuel, 2025)

PLCFishMOT: multiple fish fry tracking utilizing particle filtering and attention mechanism - Huachao Tan; Yuan Cheng; Dan Liu; Guihong Yuan; Yanbo Jiang; Hongyong Gao; Hai Bi (Aquaculture International, 2025)

Trans-Media Motion Control of a Hybrid Aerial Underwater Vehicle Considering Actuator Dynamic Input Saturation - Tongjin Wei; Yuanbo Bi; Zheng Zeng; Lian Lian; Yangwen Dan (Journal of Marine Science and Engineering, 2024)
Hybrid aerial underwater vehicles (HAUVs) have shown broad development prospects for rapid emergency response and marine scientific observation at the sea–air interface in recent decades. The trans-media motion control problem of HAUV is a special and critical problem in the HAUV field. This paper extracts the key factors of HAUV trans-media motion control: the significant changes in dynamic input saturation of the actuator and hydrodynamic force on the HAUV body during the trans-media process. In response to the issue, this paper firstly established a HAUV trans-media motion model considering actuator dynamic input saturation based on the measured HAUV trans-media test data. Then, this paper developed a control strategy for the priority attitude angle and rear heave during the trans-media process of multi-rotor HAUV, and designed a trans-media motion control algorithm that considers actuator dynamic input saturation and model uncertainty. The stability of the control algorithm was proven through Lyapunov stability theory. Finally, this paper conducted simulation verification on the designed control algorithm, and the results showed that compared with the traditional sliding mode control algorithm, this control algorithm had a significant improvement in the performance of trans-media speed control. The speed overshoot of the traditional sliding mode control algorithm was 4.25 times that of the control algorithm proposed in this paper.

Preventive and reparative potentials of heat-inactivated and viable commensal Bacillus pumilus SE5 in ameliorating the adverse impacts of high soybean meal in grouper (Epinephelus coioides) - Bi-Yun Zhang; Qing-Jie Nie; Jian-Ming Xu; Guo-He Cai; Ji-Dan Ye; Ting Jin; Hong-Ling Yang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Transcription repression of estrogen receptor alpha by ghrelin/Gq/11/YAP signaling in granulosa cells promotes polycystic ovary syndrome - Pengfei Zhu; Xingyu Bi; Dan Su; Xiaoling Li; Yanhua Chen; Zhijiao Song; Lijiang Zhao; Yaoqing Wang; Suming Xu; Xueqing Wu (Human Cell, 2024)

Nitrogenous fertilizer plays a more important role than cultivars in shaping sorghum-associated microbiomes - Fangfang Li; Anqi Sun; Xiaoyan Jiao; Dan-Ting Yu; Peixin Ren; Bing-Xue Wu; Peng He; Li Bi; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2024)

Dipodidae (Rodentia, Mammalia) from the Miocene of Damiao, Nei Mongol, China - Hai-Dan Ma; Zhao-Qun Zhang; Shun-Dong Bi (Journal of Mammalian Evolution, 2024)

The Role of BNIP3 and Blocked Autophagy Flux in Arsenic-Induced Oxidative Stress–Induced Liver Injury in Rats - Haiyan Zhi; Dingnian Bi; Dan Zheng; Qingyue Lu; Hongling Wang; Yi Wang; Ying Lv; Didong Lou; Yong Hu (Biological Trace Element Research, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

The Association Between Branched-Chain Amino Acid Concentrations and the Risk of Autism Spectrum Disorder in Preschool-Aged Children - Qi Gao; Dan Bi; Bingbing Li; Min Ni; Dizhou Pang; Xian Li; Xiaoli Zhang; Yiran Xu; Qiang Zhao; Changlian Zhu (Molecular Neurobiology, 2024)
Several studies have linked branched-chain amino acid (BCAA) metabolism disorders with autism spectrum disorder (ASD), but the results have been inconsistent. The purpose of this study was to explore the association between BCAA concentrations and the risk of ASD. A total of 313 participants were recruited from two tertiary referral hospitals from May 2018 to July 2021. Concentrations of BCAAs in dried blood spots were analyzed using liquid chromatography-tandem mass spectrometry-based analysis. Multivariate analyses and restricted cubic spline models were used to identify the association between BCAAs and the risk of ASD, and a nomogram was developed by using multivariate logistic regression and the risk was determined by receiver operating characteristic curve analysis and calibration curve analysis. Concentrations of total BCAA, valine, and leucine/isoleucine were higher in the ASD group, and all of them were positively and non-linearly associated with the risk of ASD even after adjusting for potential confounding factors such as age, gender, body mass index, and concentrations of BCAAs ( P < 0.05). The nomogram integrating total BCAA and valine showed a good discriminant AUC value of 0.756 (95% CI 0.676–0.835). The model could yield net benefits across a reasonable range of risk thresholds. In the stratified analysis, the diagnostic ability of the model was more pronounced in children older than 3 years. We provide evidence that increased levels of BCAAs are associated with the risk of ASD, and the nomogram model of BCAAs presented here can serve as a marker for the early diagnosis of ASD.

The greener the living environment, the better the health? Examining the effects of multiple green exposure metrics on physical activity and health among young students - Yuheng Mao; Tianyu Xia; Fan Hu; Dan Chen; Yichen He; Xing Bi; Yangcen Zhang; Lu Cao; Jingheng Yan; Jinyu Hu; Yanzi Ren; Hongmei Xu; et al. (Environmental Research, 2024)

Improving monitoring Karst rocky desertification using high-frequency Landsat observations: A generalized framework and its application to a typical karst region in southeast China - Xu Bi; Yao Yao; Zhongcheng Wang; Chunhua Li; Dan Cao; Li Wen; Lei Jing; Bin Sun (CATENA, 2024)

Environmental arsenic pollution induced liver oxidative stress injury by regulating miR-155 through inhibition of AUF1 - Ying Lv; Hongling Wang; Dan Zheng; Mingyang Shi; Dingnian Bi; Qian Hu; Haiyan Zhi; Didong Lou; Jun Li; Shaofeng Wei; Yong Hu (Science of The Total Environment, 2024)

Numerical study of flame characteristics in a reduced-diameter vortex combustor - Jing-hao Zhang; Ming-shu Bi; Dan Du; Yuan Wang; Jing-jie Ren (Fuel, 2024)

Spatiotemporal distribution and ecological risk assessment of pharmaceuticals and personal care products (PPCPs) from Luoma Lake, an important node of the South-to-North Water Diversion Project - Ning Wang; Guodong Kang; Guanjiu Hu; Jianqiu Chen; Dan Qi; Fengzhi Bi; Ning Chang; Zhanqi Gao; Shenghu Zhang; Weitao Shen (Environmental Monitoring and Assessment, 2023)

Effect of sourdough on the quality of whole wheat fresh noodles fermented with exopolysaccharide lactic acid bacteria - Yake Du; Zhen Dai; Tingting Hong; Qing Bi; Haoran Fan; Xueming Xu; Dan Xu (Food Research International, 2023)

Using word embedding for environmental violation analysis：Evidence from Pennsylvania unconventional oil and gas compliance reports - Dan Bi; Ju-e Guo; Erlong Zhao; Shaolong Sun; Shouyang Wang (Environmental Development, 2023)

Mongolia Contributed More than 42% of the Dust Concentrations in Northern China in March and April 2023 - Siyu Chen; Dan Zhao; Jianping Huang; Jiaqi He; Yu Chen; Junyan Chen; Hongru Bi; Gaotong Lou; Shikang Du; Yue Zhang; Fan Yang (Advances in Atmospheric Sciences, 2023)

Effects of TCPP and TCEP exposure on human corneal epithelial cells: Oxidative damage, cell cycle arrest, and pyroptosis - Zhen-Ning Zhang; Dan-Lei Yang; Hai Liu; Jue Bi; Ya-Bo Bao; Jiao-Yang Ma; Qin-Xiang Zheng; Dao-Lei Cui; Wei Chen; Ping Xiang (Chemosphere, 2023)

Effect of high-molecular weight dextran-enriched sourdough fermented using Leuconostoc mesenteroides ATCC 8293 on bread quality and gluten - Qing Bi; Tingting Hong; Xing Mei; Xueming Xu; Dan Xu (Food Bioscience, 2023)

Electricity generation in Ghana: Evaluation of crop residues and the associated greenhouse gas mitigation potential - Patience Afi Seglah; Komikouma Apelike Wobuibe Neglo; Hongyan Wang; Dan Cudjoe; Francis Kemausuor; Chunyu Gao; Yuyun Bi; Yajing Wang (Journal of Cleaner Production, 2023)

Controllable assembly of three-dimensional porous graphene-Au dual aerogels and its application for high-efficient bioelectrocatalytic O2 reduction - Tuotuo Ma; Wenjing Mu; Yarui Tang; Wenhua Bi; Wei Liu; Dan Wen (Analytica Chimica Acta, 2023)

Cross-biome soil viruses as an important reservoir of virulence genes - Li Bi; Li-Li Han; Shuai Du; Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Hang-Wei Hu (Journal of Hazardous Materials, 2023)

An improved algae-YOLO model based on deep learning for object detection of ocean microalgae considering aquacultural lightweight deployment - Dan Liu; Pengqi Wang; Yuan Cheng; Hai Bi (Frontiers in Marine Science, 2022)
Algae are widely distributed and have a considerable impact on water quality. Harmful algae can degrade water quality and be detrimental to aquaculture, while beneficial algae are widely used. The accuracy and speed of existing intelligent algae detection methods are available, but the size of parameters of models is large, the equipment requirements are high, the deployment costs are high, and there is still little research on lightweight detection methods in the area of algae detection. In this paper, we propose an improved Algae-YOLO object detection approach, which is based on ShuffleNetV2 as the YOLO backbone network to reduce the parameter space, adapting the ECA attention mechanism to improve detection accuracy, and redesigning the neck structure replacing the neck structure with ghost convolution module for reducing the size of parameters, finally the method achieved the comparable accuracy. Experiments showed that the Algal-YOLO approach in this paper reduces the size of parameters by 82.3%, and the computation (FLOPs) is decreased from 16G to 2.9G with less loss of accuracy, and mAP by only 0.007 when compared to the original YOLOv5s. With high accuracy, the smaller model size are achieved, which reduces the equipment cost during actual deployment and helps to promote the practical application of algae detection.

Long‐term series variation in fishery biology of Dosidicus gigas off Peru: Response to climate variability from 2008 to 2020 - Ya Ting Dan; Bi Lin Liu; Xin Jun Chen; Wei Guo Qian (Fisheries Oceanography, 2022)
As a cephalopod with a short life cycle, the Dosidicus gigas (jumbo flying squid) is extremely sensitive to climate variability and marine environment changes in terms of individual growth and resource changes. Based on 7514 D. gigas samples collected off Peru from 2008 to 2020, the fishery biological characteristics such as size, sexual maturity, and size‐at‐maturity were analyzed to explore the impacts of climate variability on individual growth. The results showed that there were significant differences in the relationship between mantle length and body weight and in the composition of sexual maturity between male and female individuals in different years ( P D. gigas and slowed down their sexual maturity, producing D. gigas groups in medium and large sizes; El Niño events inhibited the individual growth of D. gigas and accelerated their sexual maturity, producing D. gigas groups in a smaller size. From 2008 to 2020, the mantle length of the small‐size group decreased by 46 mm, while that of the medium‐size group increased by 28 mm. Size‐at‐maturity of female D. gigas decreased by 201.2 mm and that of male D. gigas decreased by 143 mm. The study concluded that the changes in the marine environment caused by climate variability from 2008 to 2020 have had a significant impact on the population structure, growth, and development of the D. gigas off Peru.

Identifying environmental and health threats in unconventional oil and gas violations: evidence from Pennsylvania compliance reports - Dan Bi; Ju-e Guo; Erlong Zhao; Shaolong Sun; Shouyang Wang (Environmental Science and Pollution Research, 2022)

Field investigation and numerical simulation on rockfalls in Zhangmu Town, Tibet, China - Zhong-fu Wang; Han-dong Liu; Si-ming He; Dan Bi (Journal of Mountain Science, 2022)

Dynamic behavior of rock avalanche using irregular particle discrete element method - Zhongfu Wang; Haoyuan Li; Dan Bi; Guipeng Li (Arabian Journal of Geosciences, 2022)

Assigning a grass-root NGO role to legitimate organizations as resident watch-dogs in negotiating carbon benefits derived from multilateral funding - Dan-Bi Um (International Environmental Agreements: Politics, Law and Economics, 2021)

Seismically induced changes in groundwater levels and temperatures following the ML5.8 (ML5.1) Gyeongju earthquake in South Korea - Soo-Hyoung Lee; Jae Min Lee; Sang-Ho Moon; Kyoochul Ha; Yongcheol Kim; Dan Bi Jeong; Yongje Kim (Hydrogeology Journal, 2021)
Hydrogeological responses to earthquakes such as changes in groundwater level, temperature, and chemistry, have been observed for several decades. This study examines behavior associated with M L 5.8 and M L 5.1 earthquakes that occurred on 12 September 2016 near Gyeongju, a city located on the southeast coast of the Korean peninsula. The M L 5.8 event stands as the largest recorded earthquake in South Korea since the advent of modern recording systems. There was considerable damage associated with the earthquakes and many aftershocks. Records from monitoring wells located about 135 km west of the epicenter displayed various patterns of change in both water level and temperature. There were transient-type, step-like-type (up and down), and persistent-type (rise and fall) changes in water levels. The water temperature changes were of transient, shift-change, and tendency-change types. Transient changes in the groundwater level and temperature were particularly well developed in monitoring wells installed along a major boundary fault that bisected the study area. These changes were interpreted as representing an aquifer system deformed by seismic waves. The various patterns in groundwater level and temperature, therefore, suggested that seismic waves impacted the fractured units through the reactivation of fractures, joints, and microcracks, which resulted from a pulse in fluid pressure. This study points to the value of long-term monitoring efforts, which in this case were able to provide detailed information needed to manage the groundwater resources in areas potentially affected by further earthquakes.

Growth influence of juvenile golden trout (Oncorhynchus mykiss) in different osmotic conditions: implications for tissue histology, biochemical indicators, and genes transcription involved in GH/IGF system - Baoliang Bi; Yu Gao; Dan Jia; Lingfu Kong; Yanhua Su; Hua Rong; Xiangwei Wu; Xiaowen Wang; Zhuoyong Hu; Qing Hu (Fish Physiology and Biochemistry, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Comparative transcriptome combined with morpho-physiological analyses revealed candidate genes potentially for differential cold tolerance in two contrasting apricot (Prunus armeniaca L.) cultivars - Dan Yu; Xiaojuan Liu; Yifan Cui; Quanxin Bi; Yang Zhao; Dongxing Li; Haiyan Yu; Libing Wang (Trees, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Molecular changes in solitary fibrous tumor progression - Hyung Kyu Park; Dan Bi Yu; Minjung Sung; Ensel Oh; Mingi Kim; Ji-Young Song; Mi-Sook Lee; Kyungsoo Jung; Ka-Won Noh; Sungbin An; Kyoung Song; Do-Hyun Nam; et al. (Journal of Molecular Medicine, 2019)

Determining pesticide residues in wheat flour by ultrahigh-performance liquid chromatography/quadrupole time-of-flight mass spectrometry with QuEChERS extraction - Nho-Eul Song; Dan-Bi Kim; Tae-Gyu Lim; Yun-Yeol Lee; Miyoung Yoo; Tae Gyu Nam (Food Additives & Contaminants: Part A, 2019)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Assessment of Temperature Extremes in China Using RegCM4 and WRF - Xianghui Kong; Aihui Wang; Xunqiang Bi; Dan Wang (Advances in Atmospheric Sciences, 2019)

Variants of the OLIG2 Gene are Associated with Cerebral Palsy in Chinese Han Infants with Hypoxic–Ischemic Encephalopathy - Liya Sun; Lei Xia; Mingtai Wang; Dengna Zhu; Yangong Wang; Dan Bi; Juan Song; Caiyun Ma; Chao Gao; Xiaoli Zhang; Yanyan Sun; Xiaoyang Wang; et al. (NeuroMolecular Medicine, 2019)

Occurrence of emerging mycotoxins in cereals and cereal-based products from the Korean market using LC-MS/MS - Dan-Bi Kim; Nho-Eul Song; Tae Gyu Nam; Sanghee Lee; Dongwon Seo; Miyoung Yoo (Food Additives & Contaminants: Part A, 2019)

Full Thickness Skin Expansion ex vivo in a Newly Developed Reactor and Evaluation of Auto-Grafting Efficiency of the Expanded Skin Using Yucatan Pig Model - Man-Il Huh; Soo-Jin Yi; Kyung-Pil Lee; Hong Kyun Kim; Sang-Hyun An; Dan-Bi Kim; Rae-Hyung Ryu; Jun-Sik Kim; Jeong Ok Lim (Tissue Engineering and Regenerative Medicine, 2018)

Sorbic, benzoic and propionic acids in fishery products: a survey of the South Korean market - Dan-Bi Kim; Gwang-Ju Jang; Miyoung Yoo; Gunyoung Lee; Sang Soon Yun; Ho Soo Lim; MeeKyung Kim; Sanghee Lee (Food Additives & Contaminants: Part A, 2018)

Comparative studies of bioactive organosulphur compounds and antioxidant activities in garlic ( Allium sativum L.), elephant garlic ( Allium ampeloprasum L.) and onion ( Allium cepa L.) - Sunyoung Kim; Dan-Bi Kim; Wenjie Jin; Junghyuck Park; Wonjin Yoon; Yunyeol Lee; Soyoung Kim; Sanghee Lee; Sungsoo Kim; Ok-Hwan Lee; Dongbin Shin; Miyoung Yoo (Natural Product Research, 2018)

Prognostic Utility of Fatty Acid-Binding Protein 4 in Patients with Type 2 Diabetes and Acute Ischemic Stroke - Siou Li; Pengxiang Bi; Weina Zhao; Yifei Lian; Haifu Zhu; Dan Xu; Jiayuan Ding; Quankui Wang; Changhao Yin (Neurotoxicity Research, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Controlled-source electromagnetic data processing based on gray system theory and robust estimation - Dan Mo; Qi-Yun Jiang; Di-Quan Li; Chao-Jian Chen; Bi-Ming Zhang; Jia-Wen Liu (Applied Geophysics, 2017)

The acute toxicity of bisphenol A and lignin-derived bisphenol in algae, daphnids, and Japanese medaka - Dan Li; Ran Bi; Hongxing Chen; Lei Mu; Lina Zhang; Qin Chen; Haibo Xie; Yongju Luo; Lingtian Xie (Environmental Science and Pollution Research, 2017)

Informed consent utilizing satellite imagery in forestry carbon trading with North Korea - Dan-Bi Um; Jung-Sup Um (International Environmental Agreements: Politics, Law and Economics, 2017)

Profiling of organosulphur compounds using HPLC-PDA and GC/MS system and antioxidant activities in hooker chive ( Allium hookeri ) - Sunyoung Kim; Dan-Bi Kim; Sanghee Lee; Jisu Park; Dongbin Shin; Miyoung Yoo (Natural Product Research, 2016)

A novel fusarivirus isolated from the phytopathogenic fungus Nigrospora oryzae - Jie Zhong; Si Qi Zhao; Gui Fang Li; Xi Dan Pang; Xiao Jun Deng; Hong Jian Zhu; Bi Da Gao; Qian Zhou (Virus Genes, 2016)

Association Between Osteopontin Gene Polymorphisms and Cerebral Palsy in a Chinese Population - Qing Shang; Chongchen Zhou; Dongzhi Liu; Wenxia Li; Mingjie Chen; Yiran Xu; Fei Wang; Dan Bi; Xiaoli Zhang; Xinzhi Zhao; Lei Wang; Changlian Zhu; et al. (NeuroMolecular Medicine, 2016)

Intra-regional and inter-regional abnormalities and cognitive control deficits in young adult smokers - Dan Feng; Kai Yuan; Yangding Li; Chenxi Cai; Junsen Yin; Yanzhi Bi; Jiadong Cheng; Yanyan Guan; Sha Shi; Dahua Yu; Chenwang Jin; Xiaoqi Lu; et al. (Brain Imaging and Behavior, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

Striatum morphometry is associated with cognitive control deficits and symptom severity in internet gaming disorder - Chenxi Cai; Kai Yuan; Junsen Yin; Dan Feng; Yanzhi Bi; Yangding Li; Dahua Yu; Chenwang Jin; Wei Qin; Jie Tian (Brain Imaging and Behavior, 2016)

A novel mycovirus identified from the rice false smut fungus Ustilaginoidea virens - Hong Jian Zhu; Dan Chen; Jie Zhong; Shuai Yang Zhang; Bi Da Gao (Virus Genes, 2015)

Simultaneous determination of six constituents in Mahuang Fuzi Xixin by UPLC-PDA–MS/MS - Lin Zhang; Chengying Wang; Dezu Miao; Dan Yuan; Kaishun Bi; Jingyu Yang; Libin Zhan (Natural Product Research, 2015)

Developing microsatellite markers for Geodorum eulophioides (Orchidaceae) and cross-species amplification in two sympatric, congeneric species - Ting Ying; Qi-Fang Geng; Dan-Bi Wang; Hong Liu; Jing Xu; Zi-Bing Zhang; Zhong-Sheng Wang; Yi-Bo Luo (Conservation Genetics Resources, 2014)

Inverse associations of outdoor activity and vitamin D intake with the risk of Parkinson’s disease - Dan Zhu; Gui-you Liu; Zheng Lv; Shi-rong Wen; Sheng Bi; Wei-zhi Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of dietary amylose/amylopectin ratio on growth performance, feed utilization, digestive enzymes, and postprandial metabolic responses in juvenile obscure puffer Takifugu obscurus - Xiang-he Liu; Chao-xia Ye; Ji-dan Ye; Bi-duan Shen; Chun-yan Wang; An-li Wang (Fish Physiology and Biochemistry, 2014)

Complete genome sequence and organization of a novel virus from the rice false smut fungus Ustilaginoidea virens - Jie Zhong; Jun-Zi Zhu; Xiang-Hua Lei; Dan Chen; Hong-Jian Zhu; Bi-Da Gao (Virus Genes, 2014)

Unlocking the vault: next‐generation museum population genomics - Ke Bi; Tyler Linderoth; Dan Vanderpool; Jeffrey M. Good; Rasmus Nielsen; Craig Moritz (Molecular Ecology, 2013)
Natural history museum collections provide unique resources for understanding how species respond to environmental change, including the abrupt, anthropogenic climate change of the past century. Ideally, researchers would conduct genome‐scale screening of museum specimens to explore the evolutionary consequences of environmental changes, but to date such analyses have been severely limited by the numerous challenges of working with the highly degraded DNA typical of historic samples. Here, we circumvent these challenges by using custom, multiplexed, exon capture to enrich and sequence ~11 000 exons (~4 Mb) from early 20th‐century museum skins. We used this approach to test for changes in genomic diversity accompanying a climate‐related range retraction in the alpine chipmunks ( T amias alpinus ) in the high Sierra Nevada area of California, USA . We developed robust bioinformatic pipelines that rigorously detect and filter out base misincorporations in DNA derived from skins, most of which likely resulted from postmortem damage. Furthermore, to accommodate genotyping uncertainties associated with low‐medium coverage data, we applied a recently developed probabilistic method to call single‐nucleotide polymorphisms and estimate allele frequencies and the joint site frequency spectrum. Our results show increased genetic subdivision following range retraction, but no change in overall genetic diversity at either nonsynonymous or synonymous sites. This case study showcases the advantages of integrating emerging genomic and statistical tools in museum collection‐based population genomic applications. Such technical advances greatly enhance the value of museum collections, even where a pre‐existing reference is lacking and points to a broad range of potential applications in evolutionary and conservation biology.

Scalar Flux–Gradient Relationships Under Unstable Conditions over Water in Coastal Regions - Zhongkuo Zhao; Zhiqiu Gao; Dan Li; Xueyan Bi; Chunxia Liu; Fei Liao (Boundary-Layer Meteorology, 2013)

Seismic design analysis of the country masonry school buildings in the meizoseismal area - Yuan Feng; Dan Yi; Qiong Bi (Earthquake Engineering and Engineering Vibration, 2011)

Mineral status and mechanical properties of cancellous bone exposed to hydrogen peroxide for various time periods - Dan Li; Long Bi; Guolin Meng; Jun Wang; Rong Lv; Min Liu; Jian Liu; Yunyu Hu (Cell and Tissue Banking, 2011)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

Identification of low abundance polyA-binding proteins in Arabidopsis chloroplast using polyA-affinity column - Rui-Juan Ni; Zhuo Shen; Chuan-Ping Yang; Ya-Dan Wu; Ying-Dong Bi; Bai-Chen Wang (Molecular Biology Reports, 2010)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Characteristics of transgenic tomatoes antisensed for the ethylene receptor genes LeERT1 and LeERT2 - Zhong-feng Wang; Tie-jin Ying; Ying Zhang; Bi-li Bao; Xiao-dan Huang (Journal of Zhejiang University-SCIENCE B, 2006)

Characteristics of fruit ripening in tomato mutant epi - Zhong-feng Wang; Tie-jin Ying; Bi-li Bao; Xiao-dan Huang (Journal of Zhejiang University-SCIENCE B, 2005)